Populism: Public Sphere and Discursive Practices - Kaczmarek, Tomasz (Populismo y propaganda: entre el presente y el pasado, 2020)
The noun “populism” and the adjective “populist” are controversial terms and difficult to define from the political and social point of view, which has led to numerous controversies. In the present contribution, we analyse these terms from a discursive perspective, using theoretical assumptions that are characteristic of the analysis of discourse and the pragmatics, in order to establish what the conditions and consequences of the discursive use of these terms are. For this we use a corpus of jobs made up of statements extracted from the Spanish press of the year 2018.